Rural gentrification and ageing: a case study from French countrysides - Pierre Pistre (European Regional Science Association (ERSA), 2010)
Like most developed countries, France is concerned by repopulation of its rural areas since the 1970-1980s. Analyses of census population data 2006 confirm it, and present positive dynamics far away of cities in remote country districts. These places symbolised archaism and social confinement. Today, they represent a new way of life for many heterogeneous populations, who are going to live there for familial motives, environment or economic reasons. The urban-rural migrations clearly represent main processes of sociodemographic changes in French countrysides, and in many international contexts (1). Rural gentrification is a form of migration towards rural areas, undertaken by populations of middle and upper classes from cities. They participate in deep transformations of demographic, socioeconomic and housing structures, which have been first analysed in British cases (2). Can we identify same processes in French countrysides? According to life course analyses (3), French's rural areas are also characterized by high proportion of older and retired, living and coming in country districts. What part do they play in repopulation of rural areas, mainly high incomes? Which places are particularly concerned? We propose quantitative statistical and cartographic treatments, to analyse interactions between processes of rural gentrification and ageing. We use several data resources (sociodemographic, income, housing) on whole France, with small geographic scales and aggregated areas, to realise spatial analyses of urban-rural relations and intra-rural. Our research is part of works on rural residential economy (4), in context of post-productive countryside. Indubitably, the retired are keys economic development actors, in French countrysides (5) and others. 1 Jentsch B. and al., (2009). International migration and rural areas, Ashgate. 2 Philipps M. (1993). "Rural gentrification and the processes of class colonization ", Journal of Rural Studies. 3 Détang-Dessandre C. and al., (2008).Life cycle and migration to urban and rural areas: estimation of mixed logit model on french data", Journal of regional science. 4 Davezies L. (2009). L'économie locale résidentielle", Géographie, Economie, Société. 5 Vollet D. and al., (2005).Impact of retirees on rural development: some observations from the South of France", Journal of regional analysis and policy.
Keywords: 330